Impact of 17β Estradiol on Catfish, Heteropneustes fossilis (Bloch.) - V. Ramanathan, M. Velu* and (Recent Research in Science and Technology, 2011)
Industrial and municipal sewage treatments works effluents discharges and surface run off represent the main source of synthetic and naturals estrogens into the aquatic environment. 17β estradiol (E2) is now considered as an important contaminant of the aquatic environment. Despite this, little is known about the biological effects of exposure to low concentrations of E2, or the sensitivity of different fish life stages to the disruptive effects of E2. To address these issues, the present has been conducted a series of experiments on the freshwater fish Heteropneustes fossilis (Bloch.) exposing them to low concentrations of E2 (5, 25 and 100 ng E2/l). These concentrations correspond to those commonly found in effluents and for the lower dose, a concentration found in some surface water. In the adult stage, secondary sexual characteristics, gonadal growth (the gonado-somatic index (GSI)) and sex ratio were calculated. For all experiments, the concentrations of E2 were measured by a gas chromatography–mass spectrometry (GC–MS). This study demonstrated that early life stages of the fish are sensitive to low concentrations of E2 leading to partial feminization of the population and to vitellogenin induction and highlight the effects on vulnerable developmental stages. Moreover these data raise further concerns about the effects of steroid estrogens in the environment on fish reproductive health.